2017
DOI: 10.1177/1748048516688134
|View full text |Cite
|
Sign up to set email alerts
|

Visual framing of the European refugee crisis in Der Spiegel and CNN International: Global journalism in news photographs

Abstract: Building on previous research that has theorized and operationalized the concept of global journalism, this study analyzed 287 photographs published on CNN International and Der Spiegel online news sites to examine the evidence of global journalism practices in visual news content. The results of the quantitative content analysis revealed that the transnational news outlet CNN International more frequently used close-ups and tracking shots to feature refugees in its visual reportage than the German news magazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 43 publications
1
36
0
7
Order By: Relevance
“…Although the rise of computational approaches offers promising opportunities for research on media and migration (Van Atteveldt & Peng, 2018), one limitation of textual content analysis-and therefore also most computational methods-is the neglect of visuals. Although there are some excellent examples of research on visuals (e.g., Zhang & Hellmüller, 2017), the visual dimension has yet not received the place it deserves. As argued by Graber, notably thirty years ago, (1989, p. 149), "purely verbal analyses not only miss the information contained in the pictures and nonverbal sounds, they even fail to interpret the verbal SETTING THE AGENDA FOR RESEARCH ON MEDIA AND MIGRATION content appropriately because that content is modified by its combination with picture messages".…”
Section: Limited Methodological Toolkitmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rise of computational approaches offers promising opportunities for research on media and migration (Van Atteveldt & Peng, 2018), one limitation of textual content analysis-and therefore also most computational methods-is the neglect of visuals. Although there are some excellent examples of research on visuals (e.g., Zhang & Hellmüller, 2017), the visual dimension has yet not received the place it deserves. As argued by Graber, notably thirty years ago, (1989, p. 149), "purely verbal analyses not only miss the information contained in the pictures and nonverbal sounds, they even fail to interpret the verbal SETTING THE AGENDA FOR RESEARCH ON MEDIA AND MIGRATION content appropriately because that content is modified by its combination with picture messages".…”
Section: Limited Methodological Toolkitmentioning
confidence: 99%
“…Regarding the portrayal of migration and migrants in mass media, the general focus of the literature is on aspects of salience of the issue (e.g., Boomgaarden & Vliegenthart, 2009;Greussing & Boomgaarden, 2017), the tonality with which migration or migrants are depicted in mass media (e.g., Lawlor & Tolley, 2017) and more recently in social media (e.g., Heidenreich, Eberl, Lind, & Boomgaarden, 2019;Lee & Nerghes, 2018), the framing or related stereotypical tendencies of such coverage (e.g., Greussing & Boomgaarden, 2017;Heidenreich, Lind, Eberl, & Boomgaarden, in press;Joris, d'Haenens, Van Gorp, & Mertens, 2018;Ramasubramanian & Miles, 2018), the visual representation of the issue (Zhang & Hellmüller, 2017), and the silencing of migrant voices in the news (e.g., De Cock et al, 2018;Georgiou & Zaborowski, 2017;Kluknavská, Bernhard, & Boomgaarden, 2019). In sum, one can conclude that media coverage of refugee and asylum issues is dominated by problemorientation (e.g., Cecchi, 2011;Gemi, Ulasiuk, & Triandafyllidou, 2013;Grobet, 2014;Heller, 2014;Lynn & Lea, 2003).…”
Section: The Research Literature On Media and Migrationmentioning
confidence: 99%
“…Moreover, another common research interest is that of refugee bodies and the visual composition of numbersare people who are fleeing captured as individuals, small and medium groups or as a mass exodus of people? And what kind of knowledge do these different compositions disseminate to the public (Wright, 2002;Bleiker et al, 2013;Zhang and Hellmueller, 2017;Jovičić, 2018)? In line with one important theme of this book -the construction of refugeeness and refugee crisis in the context of Nordic welfare states -I am guided by the major concerns of the aforementioned research, yet I also shift away from the fixation on the refugee body and consider other actors that play a role in the visual construction of flight in the case of Sweden (on media discourse about refugees, see chapter 7).…”
Section: Visual Construction Of Refugeenessmentioning
confidence: 99%
“…News coverage can also employ practices of cultural proximity to present the asylum seekers as suitable and 'good' victims (Szczepanik 2016), unmarking their difference through de-ethnicizing and de-muslimizing techniques (Horsti 2013). Culture-specific media story-telling characteristics as well as geographical and practical distance can influence the tone: Zhang & Hellmueller (2017) showed that the American news covering the European refugee crisis tended to involve more humanitarian views than their German counterparts.…”
Section: Refugees In the Mediamentioning
confidence: 99%